2011
DOI: 10.1179/1743132811y.0000000045
|View full text |Cite
|
Sign up to set email alerts
|

Long-term antalgic effects of repetitive transcranial magnetic stimulation of motor cortex and serum beta-endorphin in patients with phantom pain

Abstract: These results confirm that five daily sessions of rTMS over motor cortex can produce long lasting pain relief in patients with phantom pain and it might be related to an elevation of serum beta-endorphin concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
1
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 30 publications
5
100
1
6
Order By: Relevance
“…Upregulation of motor cortex excitability might therefore modulate pain perception through indirect effects on neural networks in pain-modulating areas, such as thalamic nuclei, as suggested by neuroimaging [5]. The effect on pain may also be mediated by changes in beta-endorphin levels, which have been reported to be increased after repetitive transcranial magnetic stimulation (rTMS) as measured directly in serum as in the studies of de Andrade et al [8] and Ahmed et al [9] or indirectly as in the study of Taylor et al [10] who found that naloxone pretreatment could reduce the analgesic effect of rTMS, consistent with involvement of beta-endorphin.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Upregulation of motor cortex excitability might therefore modulate pain perception through indirect effects on neural networks in pain-modulating areas, such as thalamic nuclei, as suggested by neuroimaging [5]. The effect on pain may also be mediated by changes in beta-endorphin levels, which have been reported to be increased after repetitive transcranial magnetic stimulation (rTMS) as measured directly in serum as in the studies of de Andrade et al [8] and Ahmed et al [9] or indirectly as in the study of Taylor et al [10] who found that naloxone pretreatment could reduce the analgesic effect of rTMS, consistent with involvement of beta-endorphin.…”
Section: Introductionmentioning
confidence: 80%
“…Töpper et al [31] found that the opiate antagonist naloxone abolished the rTMS-induced pain relief, which was taken as an evidence that the analgesic effect of rTMS acted via the release of endorphins. Ahmed et al [9] found an elevation of serum beta-endorphin concentration after five sessions of 20 Hz rTMS over the left-hand area of motor cortex in 17 patients with chronic phantom pain. However, serum human Dyn level was measured in the present study and we found that there was no significant interaction between real and sham groups in tested patients with visceral pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…При этом в некоторых работах проводился толь-ко один сеанс рТМС, и обезболивающее действие оцени-вали непосредственно после стимуляции [73-75, 79, 82-86]. Однако более важным результатом является доказа-тельство долговременного обезболивающего эффекта не-скольких последовательных сеансов рТМС при хрониче-ских нейропатических болях различной этиологии [87,88] и фантомных болях [89].…”
Section: болевые синдромыunclassified
“…Эффект сохранялся в течение 3 нед после завершения лечения [24]. Имеются данные о том, что эффективность использования ТКМС в лече-нии боли может быть связана с повышением содер-жания β-эндорфинов в сыворотке крови [25].…”
Section: воздействие магнитным полем: -транскраниальная магнитная стиunclassified